Climate Change Adaptation: The Institutional Context - Pant, Dhruba; Gautam, Kamal Raj (Hydro Nepal: Journal of Water, Energy and Environment, 2012)
The vulnerability of the communities to the climate change effect is expected to increase and concerted effort from all concerned at all levels has become important. Policy, plans and programs and their implementation are important in addressing the issues and effects of climate change. This paper looks into the policy, legal and institutional mechanisms and their effectiveness and weaknesses in addressing climate change adaptation through the review of the three major policies and strategies of the Nepal Government, which have bearing on the climate change issues. DOI: http://dx.doi.org/10.3126/hn.v11i1.7224 Hydro Nepal Special Issue: Conference Proceedings 2012 pp.100-105